Development of eight maize hybrids with high yield potential and competitive agronomic characteristics for the mid-altitudes of Mexico and lowland tropical of Latin-America. - CGIAR Research Program on Maize (2021)
*Confidential project* Stage 4 lowland tropical and mid-altitude hybrids were tested in three different trials across 8-10 sites in Mexico and eight hybrids were selected as candidates for advancement to Stage 5 hybrids evaluation during 2022.